An Adult Mouse Model of Vibrio cholerae-induced Diarrhea for Studying Pathogenesis and Potential Therapy of Cholera. - Sutthipong Sawasvirojwong; Potjanee Srimanote; Varanuj Chatsudthipong; Chatchai Muanprasat (Public Library of Science (PLoS), 2013)
Cholera is a diarrheal disease causing significant morbidity and mortality worldwide. This study aimed to establish an adult mouse model of Vibrio cholerae-induced diarrhea and to characterize its pathophysiology. Ligated ileal loops of adult mice were inoculated for 6, 9, 12 and 18 h with a classical O1 hypertoxigenic 569B strain of V. cholerae (10(7) CFU/loop). Time-course studies demonstrated that the optimal period for inducing diarrhea was 12 h post-inoculation, when peak intestinal fluid accumulation (loop/weight ratio of ∼0.2 g/cm) occurred with the highest diarrhea success rate (90%). In addition, pathogenic numbers of V. cholerae (∼10(9) CFU/g tissue) were recovered from ileal loops at all time points between 6-18 h post-inoculation with the diarrheagenic amount of cholera toxin being detected in the secreted intestinal fluid at 12 h post-inoculation. Interestingly, repeated intraperitoneal administration of CFTRinh-172 (20 µg every 6 h), an inhibitor of cystic fibrosis transmembrane conductance regulator (CFTR), completely abolished the V. cholerae-induced intestinal fluid secretion without affecting V. cholerae growth in vivo. As analyzed by ex vivo measurement of intestinal electrical resistance and in vivo assay of fluorescein thiocyanate (FITC)-dextran trans-intestinal flux, V. cholerae infection had no effect on intestinal paracellular permeability. Measurements of albumin in the diarrheal fluid suggested that vascular leakage did not contribute to the pathogenesis of diarrhea in this model. Furthermore, histological examination of V. cholerae-infected intestinal tissues illustrated edematous submucosa, congestion of small vessels and enhanced mucus secretion from goblet cells. This study established a new adult mouse model of V. cholerae-induced diarrhea, which could be useful for studying the pathogenesis of cholera diarrhea and for evaluating future therapeutics/cholera vaccines. In addition, our study confirmed the major role of CFTR in V. cholerae-induced intestinal fluid secretion.